Development of a reconfigurable fixture for low weight machining operations. Issue 1 (1st January 2019) - Daniyan, I. A.; Adeodu, A. O.; Oladapo, B. I.; Daniyan, O. L.; Ajetomobi, O. R.
Abstract: Fixtures are production tools used to accurately manufacture duplicate and interchangeable parts. They are specially designed so that large numbers of components can be machined or assembled identically and to ensure interchangeability of components. It eliminates problems of marking out, repetitive check or work setup, measuring and other setup before machining. In this study, a reconfigurable fixture was developed using pneumatic controllers. The materials employed for this study include; a surface plate, six double-acting cylinder, two movable frames, four 5/2-way double solenoid valves, two side brazes, four 1-way flow control valves and three manually operated switches. The design was carried out with the aid of Autodesk Inventor and simulation of the developed fixture was done using FESTO fluid SIM to test the performance of the designed circuit and pneumatic cylinders. The result obtained from the finite element analysis indicates that the clamping force is enough to withstand operational and loading forces on the workpiece because the maximum stress induced on the fixture is lower than the yield strength of the material. Hence, the fixture possesses satisfactory rigidity and strength for clamping purposes. The successful completion of this work solves the problem of flexibility in holding low weight workpiece during mass production, thereby increasing productivity and accuracy.